The Seller's right to cure under article 48 United Nations Convention on contracts for the international sale of goods - Mirambell i Fargas, Miquel (Universitat Pompeu Fabra, 2017)
In principle, contracts are enforceable mutually beneficial agreements. In the event of a breach of contract, many national, supranational, and international legal systems—as well as recent European harmonization projects on private law—turn to cure regimes for the furtherance of such (assumed) contractually generated welfare. Namely, a mandatory Nachfrist-mechanism, a hierarchy of remedies, and debtor’s (in sales law: seller’s) rights to cure—before and after performance date—are normative devices intended to perform and preserve contracts, employing purportedly better, more cost-effective remedies for breach. Discussion of the utility of these legal institutions undisputedly belongs to the debate on modern contract law. In this thesis, one of these cure-oriented devices is exhaustively analyzed: the seller’s right to cure after performance date under Article 48 CISG1. Whereas according to paragraph (1) the seller—provided that certain preconditions are met—can impose subsequent performance on the aggrieved buyer, under paragraphs (2-4) they can merely offer cure within a period of time, irrespective of any preconditions. Article 48 CISG’s systematic setting, comparative law framework, origin, forerunners, preconditions for existence—general and specific—performance in practice, legal consequences—with regards to both the breach-of-contract regime and the availability of other remedies under the CISG—, and economic-behavioural implications are exegetically analysed. A particular focus is given to the allocation of contractual risk (see epigraph 3.2.9). Finally, conclusions are drawn at two levels: one concerning the CISG’s regime and another related to general Contract law. En principio, los contratos son acuerdos ejecutables mutuamente beneficiosos. En caso de incumplimiento del contrato, muchos sistemas jurídicos nacionales, supranacionales e internacionales—así como los recientes proyectos europeos de armonización en derecho privado—recurren a regímenes de subsanación para promover el bienestar que presumiblemente se ha generado con el contrato. A saber, un mecanismo de un Nachfrist obligatorio, una jerarquía de remedios y derechos del deudor (en compraventa: del vendedor) de subsanar—antes y después de la fecha de cumplimiento—son instrumentos normativos destinados a dar cumplimiento a los contratos y a preservarlos por medio de remedios, a priori, económicamente más eficientes. La discusión sobre la bondad y utilidad de estas instituciones indudablemente pertenece al planteamiento de un derecho de contratos moderno. En esta tesis se analiza exhaustivamente uno de estos instrumentos de subsanación: el derecho del vendedor a subsanar después de la fecha de entrega en virtud del artículo 48 CISG2. Mientras que de acuerdo con su párrafo (1) el vendedor –reuniendo ciertas condiciones previas– puede imponer una ulterior ejecución al comprador perjudicado; en virtud de los párrafos (2-4), éste solamente puede ofrecer una subsanación dentro de un plazo, pero independientemente de cualquier condición previa. Del citado artículo 48 se analizan exegéticamente el entorno sistemático, el marco en derecho comparado, el origen, los precursores, las condiciones previas para la existencia—generales y específicas—, su ejecución en la práctica, las consecuencias jurídicas—en el régimen del incumplimiento del contrato y en la disponibilidad de otros remedios bajo la Convención—así como las implicaciones económicas y conductuales. Se hace una contribución en relación con la asignación del riesgo contractual (véase infra 3.2.9). Finalmente, se extraen conclusiones a dos niveles: uno enfocado al régimen de la Convención y otro relativo al Derecho de contratos en general.
Keywords: Artículo 48 CISG2; CISG; Derecho del vendedor; Seller's right

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

A Pluralist Approach to the Law of International Sales - Coetzee, Juana (Potchefstroom Electronic Law Journal, 2017)
International trade can support economic development and social upliftment. However, people are often discouraged from contracting internationally due to differences in legal systems which act as a non-tariff barrier to trade. This article focuses on the private law framework regulating international contracts of sale. During the twentieth century, the problem of diverse laws was primarily addressed by global uniform law such as the United Nations Convention on Contracts for the International Sale of Goods (CISG). However, uniform law is rarely complete and has to be supplemented by national law, trade usage or party agreement. Because of gaps that exist in the CISG the Swiss government made a proposal for a new global contract law. But is this a feasible solution to the fragmentary state of international trade law? In Europe, signs of reluctance are setting in towards further harmonisation efforts. The Proposal for a Common European Sales Law (CESL) was recently withdrawn, and now Britain has voted to leave the European Union; rumour having it that more countries might follow. The current private law framework for international sales contracts consists of a hybrid system where international, national, state and non-state law function side by side. This article submits that universalism is not per se the most efficient approach to the regulation of international sales law and that economic forces require a more varied approach for business-to-business transactions. The biggest challenge, however, would be to manage global legal pluralism. It is concluded that contractual parties, the courts and arbitral tribunals can effectively manage pluralism on a case-by-case basis.
Keywords: Global legal pluralism; Legal harmonisation; international contracts; international sales; unified law

Oiling the machine: overriding mandatory provisions and public policy in the Hague Principles on Choice of Law in International Commercial Contracts - Dickinson, Andrew (Uniform Law Review, 2017)
Art. 11 of the Principles on Choice of Law in International Commercial Contracts, adopted by the Council of the Hague Conference in March 2015 contains provisions governing the relationship between the system of law1 chosen by the parties under Art. 2(1) (the “chosen law”) and the laws and policies of other systems. It provides as follows: 1. These Principles shall not prevent a court from applying overriding mandatory provisions of the law of the forum which apply irrespective of the law chosen by the parties. 2. The law of the forum determines when a court may or must apply or take into account overriding mandatory provisions of another law. 3. A court may exclude application of a provision of the law chosen by the parties only if and to the extent that the result of such application would be manifestly incompatible with fundamental notions of public policy (ordre public) of the forum. 4. The law of the forum determines when a court may or must apply or take into account the public policy (ordre public) of a State the law of which would be applicable in the absence of a choice of law. 5. These Principles shall not prevent an arbitral tribunal from applying or taking into account public policy (ordre public), or from applying or taking into account overriding mandatory provisions of a law other than the law chosen by the parties, if the arbitral tribunal is required or entitled to do so. In brief summary, therefore, the first and third paragraphs address the relationship between the chosen law and certain laws and policies of the forum, the second paragraph addresses the relationship between the chosen law and certain laws of legal systems other than the forum, the fourth paragraph addresses the relationship between the chosen law and the certain policies of the legal system whose laws would have applied but for the parties’ choice under Art. 2(1) and the fifth paragraph addresses the limits of the application of the chosen law in arbitration proceedings.